Pengembangan Aplikasi Sistem Informasi Laboratorium Menggunakan Metode Timeboxing - Tantri Hidayati Sinaga (LKP Unity Academy, 2025)
Problems in managing schedules, lecturers, inventories, and laboratory rooms often lead to administrative inefficiencies in educational institutions. This study aims to develop a web-based laboratory information system application using the timeboxing method as a software development approach. The main research question formulated is: how can the timeboxing method improve the effectiveness and efficiency of developing a laboratory management application? The research methodology includes needs analysis, system design, module implementation (laboratory, lecturer, inventory, schedule), and functional testing. Each module was developed through weekly sprints with fixed time constraints. The implementation results show that the application meets user needs with a responsive form design, integrated data structure, and reliable functionality. Timeboxing proved effective in managing development time, avoiding scope creep, and maintaining team focus. The conclusion of this study is that the systematic use of the timeboxing method can produce a ready-to-use, efficient, and high-quality laboratory management application.